Prognostic predictors in polytraumatized children and their impact on outcome - Essa, Ahmed Abdelhady; El-Shaboury, Islam M.; Ibrahim, Mohammed A.; Abdelgwad, Emadeldien A.; Gadelrab, Mohammed A. (International Surgery Journal, 2017)
Background: Trauma is the leading cause of death and disability in children ≥ 1 year of age. More than 80% of injuries are caused by blunt trauma. Most seriously injured children have multiple injuries. Injury scoring systems are designed to accurately assess injury severity, appropriately triage the injured, and develop and refine trauma patient care. The pediatric trauma scoring (PTS) was devised specifically for the triage of pediatric trauma patients. The pediatric trauma scoring (PTS) was devised specifically for the triage of pediatric trauma patients. The PTS is calculated as the sum of individual scores from six clinical variables. The variables include weight, airway, systolic blood pressure (SBP), central nervous system (CNS) status (level of consciousness), presence of an open wound, and skeletal injuries. Other predicting factors for morbidity and mortality in polytraumatised children include age and gender of the patients, trauma type, arrival interval time, Glasgow Coma Scale (GCS), respiratory rate, heart rate, hematocrit value at admission. These factors can further help to prevent mortality. The objectives of this study were to assess the prognosis of polytraumatised pediatric patients by evaluation of pediatric trauma scoring system and clinical predictors of morbidity and mortality as prognostic predictors of trauma in pediatric patients. Methods: This was adescriptive study, included 60 polytraumatised pediatric patients who were attended emergency department in Suez Canal University Hospital, Ismailia, Egypt. Results: This study showed that the mean of the pediatric trauma scoring system was 10±2. According to the nature of the most severe injury, this study showed that 43 % of injuries among patients were of extremities and pelvis nature. According to length of resuscitation time among patients, this study showed that the mean time of resuscitation was 35.5±8.23 minutes. According to the type of treatment done for the patients, this study showed that 72% of the patients didn't need surgical intervention. This study showed that regarding the final outcome of the patients, 68% of the patients were admitted to inpatient. Conclusions: This study showed that both heart rate and respiratory rate had good sensitivity while both of them had lower specificity. This study showed that GCS good specificity and fair sensitivity. Regarding the PTS, this study showed that PTS had the highest specificity and the highest sensitivity among all the predictors.